PROSPEK PEMBERLAKUAN HUKUM ADAT DALAM HUKUM PIDANA NASIONAL - Vincentius Patria Setyawan (Justitia et Pax, 2019)
This study aims to determine the existence of customary law specifically related to customary offenses in national criminal law and its implementation that has been applied so far, and to find out the prospects for its application after the HP bills have been implemented. The results of this research are to provide an overview of present and future.